2020
DOI: 10.1002/ijgo.13297
|View full text |Cite
|
Sign up to set email alerts
|

What is the normal range of obstetric shock index in the immediate postpartum period in a low‐resource setting?

Abstract: Objective To determine the normal range of shock index (SI), blood pressure (BP), mean arterial pressure (MAP) and heart rate (HR) among postpartum women in a low‐resource setting. Methods In a prospective cohort study, vital signs were recorded 1 hour after delivery among postpartum women with normal blood loss who delivered in Abakaliki, Nigeria, from April to July 2019. Results Among 225 women, the median (95% reference range) was 120 (100–155.8), 70 (60–94), and 90 (66.5–116.6) mm Hg for systolic BP, diast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
1
0
1
Order By: Relevance
“…In this study of a general population of women with vaginal childbirth, we found a distribution of SI values early postpartum similar to those found in previous analyses of postpartum SI values conducted on selected populations of women without PPH. [13][14][15][16] The SI values we report were also close to those reported during pregnancy 40 and higher than those reported in young adults. 5,6 Regarding the performance of SI for predicting PPH, comparing our results with the literature is challenging, as the previous studies used populations, outcomes, SI measurement times and methods that were different from ours.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study of a general population of women with vaginal childbirth, we found a distribution of SI values early postpartum similar to those found in previous analyses of postpartum SI values conducted on selected populations of women without PPH. [13][14][15][16] The SI values we report were also close to those reported during pregnancy 40 and higher than those reported in young adults. 5,6 Regarding the performance of SI for predicting PPH, comparing our results with the literature is challenging, as the previous studies used populations, outcomes, SI measurement times and methods that were different from ours.…”
Section: Discussionsupporting
confidence: 87%
“…In this study of a general population of women with vaginal childbirth, we found a distribution of SI values early postpartum similar to those found in previous analyses of postpartum SI values conducted on selected populations of women without PPH 13–16 . The SI values we report were also close to those reported during pregnancy 40 and higher than those reported in young adults 5,6 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The possible reason for the similarities might be the systolic blood pressures obtained are higher than the heart rates. The finding of this study regarding the shock index range after childbirth is similar to the findings of the study conducted by Nwafor et al (2020) on what is the normal range of obstetric shock index in the immediate postpartum period in a low resource setting, in Abakiliki, Nigeria. The possible reasons for the similarities recorded in both studies might be owing to the conduct of the studies in the same geographic location and low resource settings.…”
Section: Discussionsupporting
confidence: 86%
“…В на-шем пилотном исследовании оценка родильниц с ПРК в зависимости от кровопотери в процентах от ОЦК продемонстрировала, что ОК в группе с ПРК был > 500 мл и составил 880 (697-1171) мл, что согласуется с общепринятыми методами диагностики кровопотери. Однако мы не выявили ни у одной из этих пациенток нарушения гемодинамики или увеличения ШИ выше 0,9, который является верхней границей нормы показателей ШИ у беременных в доношенном сроке [20][21][22].…”
Section: Discussionunclassified